Internationalization in U.S. universities: history, philosophy, practice, and future - Morosini, Marilia; Somers, Patricia; Rodriguez, Arinda; Rodriguez, Janet Solis (Educação, 2017)
In response to the global economy, universities around the world have increased internationalization efforts. This article focuses on internationalization in U. S. universities, discussing the history, presenting models and examples, reviewing the extent of internationalization on U.S. campuses. We end with a discussion on the rationales, the political realities of the new nationalism, the competition among Western universities for rankings that emphasizes high-profile internationalization, the current political questions affecting internationalization and the future of the field. While our focus is on the United States, many of the concepts and theories we discuss apply to other countries as well. ***Internacionalização em universidades dos EUA: história, filosofia, prática e futuro*** Como resposta à economia global, as universidades ao redor do mundo vêm incrementando seus esforços para se internacionalizaram. Este artigo tem como foco a internacionalização de universidades dos Estados Unidos discutindo a história, apresentando modelos e exemplos e examinando a presença da internacionalização no campus americano. Concluímos com a discussão sobre as racionalidades, as realidades políticas do novo nacionalismo, as argumentações acadêmicas contra as universidades do ocidente que enfatizam os altos perfis internacionais, as atuais questões políticas que afetam a internacionalização e o futuro do campo. Apesar do foco deste trabalho ser os Estados Unidos, muito dos conceitos e teorias discutidas podem ser aplicados para outros países.